دور الإلتزام التنظيمي والفاعلية التنظيمية في تعزيز الميزة التنافسية للمنظمة دراسة حالة على شركة جود للأدوات الكهربائية - لايقة هشام (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدف البحث إلى معرفة مستوى كل من الإلتزام التنظيمي والفاعلية التنظيمية والميزة التنافسية في المنظمة وطبيعة العلاقة بين الإلتزام التنظيمي والفاعلية التنظيمية وكذلك قياس أثر كل من الإلتزام التنظيمي والفاعلية التنظيمية في تعزيز الميزة التنافسية للمنظمة، حيث اتبع الباحث المنهج الارتباطي في مناقشة الأثر والعلاقة التي تربط مجموعة من المتغيّرات بأخرى، كما استخدمت الاستبانة لجمع البيانات من عينة البحث (العاملين في شركة جود للأدوات الكهربائية) وذلك باستخدام الحزمة الإحصائية (SPSS). وقد خلص البحث إلى أن هناك مستوى مرتفع من الإلتزام الأخلاقي لدى العاملين للبقاء في الشركة رغم الصعوبات الناتجة عن العمل في الظروف الحالية، ومستوى بين المتوسط والمنخفض فيما يتعلق بتقديم خدمات جديدة ومستوى الخدمات المقدمة حالياً، واهتمام بدرجة مرتفعة بتعزيز الميزة التنافسية في الشركة، وأن هناك مستوى متوسط للالتزام التنظيمي للعاملين، وأن هناك مستوى متوسط للفاعلية التنظيمية في الشركة، كما يوجد أثر دال إحصائيًا عند مستوى(0.05) للفاعلية التنظيمية في تعزيز الميزة التنافسية، كما يوجد أثر دال إحصائياً عند مستوى(0.05) للالتزام التنظيمي في تعزيز الميزة التنافسية للشركة، وتوجد علاقة ذات دلالة معنوية بين الفاعلية التنظيمية والإلتزام التنظيمي، كما يوجد أثر تفاعلي متبادل ذو دلالة إحصائية للفاعلية التنظيمية والإلتزام التنظيمي في تعزيز الميزة التنافسية. The objective of the research is to determine the level of organizational commitment, organizational effectiveness, competitive advantage in the organization, and the nature of the relationship between organizational commitment and organizational effectiveness, as well as measuring the impact of organizational commitment and organizational effectiveness in enhancing the competitive advantage of the organization. The questionnaire was used to collect data from the sample (workers at Joud Company tools electrical) using the statistical package (SPSS). The research concluded that there is a high level of ethical commitment of the employees to stay in the company despite the difficulties resulting from working under the current conditions, the level between the medium and low in terms of providing new services and the level of services currently provided, and a high interest in enhancing the competitive advantage in the company, The average level of organizational commitment of employees is that there is an average level of organizational effectiveness in the company. There is also a statistically significant effect at (0.05) level of organizational effectiveness in enhancing competitive advantage. There is also a statistically significant effect at (0.05) Competitive company, and there are significant differences between organizational effectiveness and organizational commitment to the relationship, and there is an interactive effect of mutual statistically significant organizational effectiveness and organizational commitment to strengthening the competitive advantage.